2019
DOI: 10.29115/sp-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Improving Response Rates in an Emergency Department Setting – A Randomized Feasibility Study

Abstract: Standard single survey mode approaches, such as mail-only or telephone-only, generally produce lower response rates than sequential mixed mode (SMM) approaches. SMM approaches may be particularly important when lower response propensities and/or poor contact information exist, as with emergency department (ED) patients. Results were examined from a randomized feasibility study testing five survey administration modes among ED patients who are discharged-to-community. A total of 4,017 discharged patients from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Four large‐scale experiments conducted in 2014, 2016 (two experiments), and 2018, tested the survey among patients from 12 hospitals, 50 hospitals, eight hospitals, and 16 hospitals, respectively. The primary aims of these experiments were to test mode protocols for survey administration and to test performance of survey items and modes of survey implementation; results are described elsewhere 12–15 . Item performance results informed the refinement of the survey instrument; item performance results from the 2018 experiment are described here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four large‐scale experiments conducted in 2014, 2016 (two experiments), and 2018, tested the survey among patients from 12 hospitals, 50 hospitals, eight hospitals, and 16 hospitals, respectively. The primary aims of these experiments were to test mode protocols for survey administration and to test performance of survey items and modes of survey implementation; results are described elsewhere 12–15 . Item performance results informed the refinement of the survey instrument; item performance results from the 2018 experiment are described here.…”
Section: Methodsmentioning
confidence: 99%
“…The primary aims of these experiments were to test mode protocols for survey administration and to test performance of survey items and modes of survey implementation; results are described elsewhere. [12][13][14][15] Item performance results informed the refinement of the survey instrument; item performance results from the 2018 experiment are described here. Mode protocol results informed CMS' recommendation that the EDPEC DTC survey is administered in one of three modes: (1) standard mixed mode (mail with telephone follow-up), (2) web survey (by email invitation) with telephone follow-up, and (3) web survey (by email invitation) followed by a mailed survey with telephone follow-up.…”
Section: Large-scale Field Experimentsmentioning
confidence: 95%
“…The overall response rate to the on-site survey was very low, but exceeded that of a web-based survey (10% for on-site vs. 5% web survey). 42 Another study tested the use of tablets to administer in-person surveys to parents of hospitalized children while they were waiting to be discharged, and found a substantially higher response rate for this protocol than to mail administration (71% tablet administration vs. 16% mail). 40 Tablet respondents were significantly more likely to be fathers, more likely to have a high school education or less, less likely to be White, and more likely to be publicly insured than mail respondents.…”
Section: In-person Modementioning
confidence: 99%
“…In this paper, we examine a patient experience survey of hospital-based emergency department (ED) patients discharged to home after their ED visit (rather than admitted to the hospital), referred to as discharged-to-community (Parast et al 2019) patients. As previous studies have found very low survey response rates among such patients, less than 20% (Mathews et al 2019;Weinick et al 2014), we sought to understand how response rates could be improved in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the ED DTC population has shown that single-mode protocols, such as mail-only or web-only, and distribution within the ED do not perform well (1-14% response rate), but sequential mixed-mode approaches may have promise (Mathews et al 2019;Parast et al 2019). In this paper, we describe results from a randomized test of nine experimental survey administration protocols, eight of which began with an invitation to a web survey, then followed by a mailed survey, a telephone survey or both.…”
Section: Introductionmentioning
confidence: 99%